Analysis of the Characteristics and Influencing Factors of Gas Explosion in Heading Face - Xue-bo Zhang; Jian-liang Gao; Jing-zhang Ren; Chun-xia Wang (Shock and Vibration)
In order to accurately grasp the characteristics and influencing factors of gas explosion in heading face, the mathematical model of gas explosion was determined. According to the actual size of a heading face of a coal mine, a 3D geometric model with a length of 100 m was established, and the effects of ignition energy and gas explosion equivalent on the gas explosion characteristics of the heading face were analyzed. The results show the following. (1) The mathematical models for numerical simulation of gas explosion can accurately simulate the gas explosion and its propagation process. The time-space step size has a great influence on the simulation results. The grid spacing for numerical simulation of mine gas explosion is determined to be 0.1 m and the time step length is determined to be 0.001 s. (2) The ignition energy has a limited effect on gas explosion characteristics. It only has a certain influence on the gas explosion process, but has little influence on the overpressure of shock wave. The larger the ignition energy is, the faster the explosion reaction speed is, and the maximum overpressure increases slightly. When the ignition energy increases to a certain value, the time of peak shock wave and the maximum overpressure both tend to be stable. The ignition energy has little effect on gas explosion characteristics when an explosion accident occurs underground with a large amount of gas accumulation. (3) The gas explosion equivalent has a great influence on the overpressure of gas explosion shock wave. The higher the explosion equivalent is, the greater the pressure is, and the peak value of the shock wave overpressure increases with the explosion equivalent as a power function. The research results have important guiding significance for the research and development of new technology for prevention and control of gas explosion.